Where am I eating? : - Timmerman, Kelsey (Wiley, 2014)
Where Am I Eating? bridges the gap between global foodproducers and the American consumer, providing an insightful lookat how our eating habits affect farmers and fishermen around theworld. Follow the author on his global quest to meet the workersthat nurture, harvest, and hunt our food, as he works alongsidethem—loading lobster diving boats in Nicaragua, harvestingbananas in Costa Rica, lugging cocoa beans in Ivory Coast with amodern-day slave, picking coffee beans in Colombia and haulingtomatoes in Indiana. This new edition includes a study guide, adeeper explanation of the "glocal" concept, and advice for studentslooking to become engaged as both local and global citizens.Arguing neither for nor against globalization, this book simplyexplores the lives of those who feed us.